Short-term Peripheral Auditory Effects of Cranial Irradiation: A Mouse Model. (November 2015) - Gasser Rutledge, Krysta L.; Prasad, Kumar G.; Emery, Kara R.; Mikulec, Anthony A.; Varvares, Mark; Gratton, Michael Anne
Objectives: Assess postcranial irradiation: (1) short-term threshold shift, (2) short-term peripheral auditory histopathology, and (3) the mouse as an experimental model. Methods: Adult mice were exposed to single-dose radiation of 10 to 60 Gy. Pre- and post-irradiation (baseline, 2-8 days) audiometric brainstem response data were recorded with analysis of cochlear ultrastructure. Results: Significant threshold shift occurred at all test frequencies in mice exposed to ≥20 Gy at 4 to 6 days post-irradiation. Ultrastructurally in Rosenthal's canal and the spiral lamina, neuronal density and extracellular matrix decreased dramatically. There was overall preservation of hair cells, stria vascularis, and vasculature. No difference within Gy group was noted in the frequency or severity of pathology along the length of the cochlea. Conclusions: The initial impact of radiation in the first week post-exposure focuses on spiral ganglion cell bodies and peripheral projections, resulting in significant threshold shift for irradiation dosages ≥20 Gy. This study demonstrates that the mouse is a viable model for study of short-term peripheral auditory effects using single-dose cranial irradiation. Additionally, with access to a precise animal irradiator, the mouse may be used as an experimental model for a fractionated irradiation dosage of 10 Gy, simulating stereotactic therapeutic cranial irradiation.